Agreement between the Denver II and Parents’ Evaluation of Developmental Status tests, with and without the assistance of a table of categorical responses - Arief Priambodo; Meita Dhamayanti; Eddy Fadlyana (Indonesian Pediatric Society, 2016)
Background Among standardized developmental screening tools, the Denver II is commonly used by Indonesian pediatricians, but the Parent’s Evaluation of Developmental Status (PEDS) test has gained in popularity. The Denver II test is filled by physicians, while the PEDS test is meant to be filled by parents. From a practical standpoint, however, parents often require assistance from doctors when filling out the PEDS forms. Hence, the advantage of the PEDS test over the Denver II test is not fully realized.Objective To compare the agreement between Denver II and PEDS tests, with and without parental use of a table of categorical responses taken from the PEDS manual.Methods We conducted a cross-sectional study in children aged 6 months to 5 years in Bandung from November 2015 to March 2016. Subjects were divided into two groups using block randomization. One group of subjects’ parents filled the PEDS questionnaires with the assistance of a table of categorical responses taken from the PEDS manual, while the other group of subjects’ parents filled PEDS forms without this table. All subjects underwent Denver II screening by pediatricans. The agreement between the PEDS and Denver II results were assessed by Kappa score.Results Of 254 children, 239 were analyzed. Kappa scores between the Denver II and PEDS tests were 0.05 (95%CI: -0.10 to 0.20) without the table of categorical responses, and -0.06 (-0.23 to 0.10) with the table of categorical responses.Conclusion Agreement between the Denver II and PEDS tests is poor. The table of categorical responses does not increase the agreement between Denver II and PEDS.